2021
DOI: 10.1111/tri.13804
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of direct oral anticoagulants under long‐term immunosuppressive therapy after liver, kidney and pancreas transplantation

Abstract: Summary The safety of direct oral anticoagulants (DOACs) in patients after solid organ transplantation (SOT) is not well defined. This study aimed at describing the safety and efficacy of DOACs in patients after SOT. Patients after kidney and/or liver transplantation under maintenance immunosuppression treated with rivaroxaban (n = 26), apixaban (n = 20) and edoxaban (n = 1) were included. Clinical data were collected retrospectively and using a questionnaire. DOAC plasma levels and thrombin generation (TG) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Existing literature regarding DOAC use in RTR involves small populations, often with low bleeding events limiting conclusions on safety [ 11 , 14 17 ]. Other studies pool multiple transplant types, limiting interpretation of results in RTR [ 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature regarding DOAC use in RTR involves small populations, often with low bleeding events limiting conclusions on safety [ 11 , 14 17 ]. Other studies pool multiple transplant types, limiting interpretation of results in RTR [ 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 recipients included, 6 had TAC dose adjustments after DOAC initiation complicating the interpretation of these results. 21 Conversely, a prospective study evaluating 11 heart transplant recipients did not find a significant change in TAC (n ¼ 3) or cyclosporine (n ¼ 8) troughs after initiating RIVA. 23 The aim of the current study was to further investigate whether RIVA/APIX affect TAC troughs in solid organ transplant recipients.…”
Section: Introductionmentioning
confidence: 93%
“…Within the limited available literature, there is conflicting evidence as to whether DOACs alter TAC pharmacokinetics. [20][21][22][23][24] A 22-patient subgroup analysis of a single-center, retrospective study of solid organ transplant recipients demonstrated that concomitant use of TAC and RIVA significantly increases TAC dose-adjusted trough concentration by 9.2% (P ¼ 0.042). 20 Another study observed a non-statistically significant (P ¼ 0.78) mean increase of 16.5% in TAC troughs in 20 recipients who received DOACs after transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Bei Nierentransplantierten und VHF sollten die gleichen Therapiestandards zur SSE-Prophylaxe Anwendung finden wie Patienten mit entsprechender CKD ohne Transplantation [1]. Mögliche Interaktionen mit dem Metabolismus der Immunsuppressiva und entsprechende Indikationen zur Spiegelbestimmung sollten beachtet werden [13,14]. Deutlich limitiert ist die Datenlage zu Patienten mit einem nephrotischem Syndrom und VHF.…”
Section: Patienten In Speziellen Situationen Der Chronischen Nierener...unclassified